Analysis of the Relationships between Type 2 Diabetes Status, Glycemic Control, and Neuroimaging Measures in the Diabetes Heart Study Mind - Raffield, Laura M. (Acta Diabetol, 2015)
AIMS: To examine the relationships between type 2 diabetes (T2D) status, glycemic control, and T2D duration with magnetic resonance imaging (MRI)-derived neuroimaging measures in European Americans from the Diabetes Heart Study (DHS) Mind cohort. METHODS: Relationships were examined using marginal models with generalized estimating equations in 784 participants from 514 DHS Mind families. Fasting plasma glucose, glycated hemoglobin, and diabetes duration were analyzed in 682 participants with T2D. Models were adjusted for potential confounders, including age, sex, history of cardiovascular disease, smoking, educational attainment, and use of statins or blood pressure medications. Association was tested with gray and white matter volume, white matter lesion volume, gray matter cerebral blood flow, and white and gray matter fractional anisotropy and mean diffusivity. RESULTS: Adjusting for multiple comparisons, T2D status was associated with reduced white matter volume (p=2.48 × 10(−6)) and reduced gray and white matter fractional anisotropy (p≤0.001) in fully adjusted models, with a trend towards increased white matter lesion volume (p=0.008) and increased gray and white matter mean diffusivity (p≤0.031). Among T2D affected participants, neither fasting glucose, glycated hemoglobin, nor diabetes duration were associated with the neuroimaging measures assessed (p>0.05). CONCLUSIONS: While T2D was significantly associated with MRI-derived neuroimaging measures, differences in glycemic control in T2D affected individuals in the DHS Mind study do not appear to significantly contribute to variation in these measures. This supports the idea that presence or absence of T2D, not fine gradations of glycemic control, may be more significantly associated with age-related changes in the brain.